A complicated relationship: Family involvement in the top management team and post-IPO survival. Issue 1 (March 2017) - Cirillo, Alessandro; Mussolino, Donata; Romano, Mauro; Viganò, Riccardo
Abstract: This exploratory study aims to analyse how and whether family involvement in the top management team of listed family firms affects post-IPO survival on capital markets. We tested our hypotheses on a data set of listed family firms over the period 2000–2011 using survival analysis. Our findings suggest that a higher number of family members in the top management team reduces the likelihood of post-IPO survival, but the relationship is affected by a family member as CEO. The number of generations is also negatively correlated with survival.